Current recommendations for footbath solutions renewal rates in dairy cattle: the need for adaptation?. (5th November 2018) - Ariza, J. M.; Bareille, N.; Oberle, K.; Guatteo, R.
Abstract : Footbaths represent a potentially useful strategy for the prevention of claw infectious diseases by treating a large number of animals concomitantly. Nevertheless, under field conditions, footbath solutions are exposed to increasing number of animal passages and therefore, to different volume losses and concentrations of manure contamination which could alter their presumed bactericidal activity. Across increasing number of cow passages, the organic matter (OM) concentration, the microbial load (ML) and the residual volumes were assessed in six commercial farms. The results indicate that the OM concentration and ML increased linearly with the number of passages of animals, and with the number of defecations in the footbath. The OM concentrations and the ML were not impacted by the farm's feet hygiene status (clean, fair and dirty), suggesting that probably the increasing number of cow passages and defecations influenced more the contamination of footbaths than the hygiene of the feet. In all the farms the volumes decreased drastically after 200 cow passages (50%). The OM concentrations after 150 and 200 cow passages did not exceed the regulatory concentrations in which disinfectant products should demonstrate to still be effective (20 g/l), and coincide with the often advised renewal rates. The findings of this study suggested that beyond the footbath contamination by OM, the renewal rates must be mainly adapted according to the remaining volume to guarantee that the entire foot is covered and therefore assure the topical action of the solution. This study highlights the importance of footbath designs for the successful implementation of these strategies in practice.